Sudden Death in a 7-year-old Child Due to Neoplasm: A Case Report - Delighta Marilyn; S. Rajan; P.S. Varghese; Tirumalae Rajalakshmi; Sukumar Sanjay (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Non-Hodgkin’s lymphoma (NHL) comprises many hematologic malignancies presenting commonly as an intrathoracic or mediastinal mass. Case Report: Here we report a case of sudden death in a 7-year-old girl resulting from NHL diagnosed after autopsy. The disease had extensive extra nodal involvement, including the heart; however, the child was surprisingly asymptomatic. Conclusion: The prognosis of children diagnosed with NHL is reported as very good, even in those with advanced disease, but a delay in presentation of the disease led to a delay in diagnosis and treatment in this case.